EVALUASI PEMANFAATAN HASIL ASESMEN DIAGNOSTIK UNTUK PERENCANAAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR: STUDI KASUS DI SDN SITIREJO, KABUPATEN BLORA - Rahmawati; Isdaryanti, Barokah; Isnaeni, Wiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Diagnostic assessment is intended to provide elementary school teachers with information about students' initial competencies and characteristics before learning is planned, yet the extent to which these results are translated into differentiated lesson planning is often unclear in classroom practice. This study aims to evaluate how the results of diagnostic assessment are utilized by teachers in planning differentiated learning at SDN Sitirejo, Blora Regency, focusing on the alignment between diagnostic assessment data and the design of learning objectives, activities, materials, and assessment. A descriptive-qualitative case study approach was employed, with teachers and students involved in the implementation of diagnostic assessment and differentiated learning as the research subjects. Data were collected through semi-structured interviews with classroom teachers, classroom observation, and document analysis of lesson plans (RPP/modul ajar), and credibility was established through source and technique triangulation. The findings show that teachers regularly conducted diagnostic assessment at the beginning of learning, in the form of oral questioning or simple quizzes. However, the results were not systematically used to group students, design differentiated materials or tasks, or provide enrichment for high-achieving students, as reflected in lesson plans that still set uniform objectives, materials, and assessment instruments for all students. This condition was mainly caused by teachers' limited time and the absence of technical guidance at the school level for following up on diagnostic assessment results. These findings indicate the need for structured mentoring and practical guidelines so that diagnostic assessment results can be optimally utilized in differentiated learning planning in elementary schools.